2010
DOI: 10.1037/a0020072
|View full text |Cite
|
Sign up to set email alerts
|

Training professional psychologists in school-based consultation: What the syllabi suggest.

Abstract: This article reports the findings from consultation syllabi from 25 American Psychological Associationapproved school psychology programs (40% response rate). Most responding programs offered 1 consultation course and many programs' syllabi stated expecting students to conduct 1 consultation case. The analysis showed most syllabi listed training in multiple models of consultation, with almost all mentioning the problem-solving model. Almost all syllabi listed training in treatment, but fewer than half suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 41 publications
(51 reference statements)
7
50
0
Order By: Relevance
“…Investigations regarding school-based consultation training practices have pointed to deficiencies in applied consultation experiences, supervision practices, and attention given to process issues (Anton-LaHart & Rosenfield, 2004;Hazel et al, 2010). Data from the current study provide preliminary evidence that a gap in consultation training practices such as supervision may be problematic.…”
Section: Considerations For Consultation Training and Supervision Pramentioning
confidence: 66%
See 4 more Smart Citations
“…Investigations regarding school-based consultation training practices have pointed to deficiencies in applied consultation experiences, supervision practices, and attention given to process issues (Anton-LaHart & Rosenfield, 2004;Hazel et al, 2010). Data from the current study provide preliminary evidence that a gap in consultation training practices such as supervision may be problematic.…”
Section: Considerations For Consultation Training and Supervision Pramentioning
confidence: 66%
“…Both Anton-LaHart and Rosenfield (2004) and Hazel et al (2010) found that courses tended to cover a variety of models of consultation rather than honing in on a particular model in depth. Both sets of authors suggested that a broad focus may be detrimental to consultation training, especially when combined with inconsistent or superficial supervision practices.…”
Section: Models Content and Processmentioning
confidence: 96%
See 3 more Smart Citations